Paraganglioma of the urinary bladder mimicking a urothelial carcinoma: a case report - Öztürk, Çiğdem; Güçer, Hasan; Çetinkaya Altuntaş, Seher; Okcu, Oğuzhan (The European Research Journal, 2023)
Paragangliomas of the urinary bladder are rare tumors and can mimic urothelial carcinomas due to some features and can be misdiagnosed. A 71-year-old female was seen for hematuria and there was a solid lesion that measured 3 cm on the urinary bladder at cystoscopy. Treatment approaches for paraganglioma and urothelial carcinoma are very different from each other; therefore differential diagnoses should be made carefully. Although immunohistochemical studies are helpful in differential diagnosis, they may cause misdiagnosis in some cases. In this article, we will discuss the clinical, histomorphological, and immunohistochemical differences between paraganglioma and urothelial carcinomas under their differential diagnosis.